Khazanah Livecast - Sunday Star (2008)
The last lecture in the Khazanah Global Lecturer series will be telecast live on March 21, at 8.30pm. Nissan Motor Company Ltd CEO, Carlos Ghosin, will be delivering the lecture, Universities perticipating are Universiti Putra Malaysia. Universiti Tenga Nasional and Universiti Teknologi Malaysia.